Rekomendasi Pemilihan Barang pada Parcel dengan Algoritma Harmony Search - Hendry Setiawan; Kevin Putra Wardojo; Oesman Hendra Kelana (Jurnal Buana Informatika, 2019)
Abstract. A parcel containing a variety of items, is a gift given to someone who has a relationship with the giver. The contents of the parcel vary, can be in the form of food, drinks, cakes, fruit, sweets, and others. In some supermarkets, generally before the commemoration of a certain day, Parcel has been provided with various contents in the price that has been set. But commonly the buyers want to package the Parcel with different content and price. To facilitate the search for the contents of the parcel based on these prices, the Harmony Search algorithm is used. Search development is carried out with consideration of basket size, item categories, and percentages of each category Evaluation of the aesthetic value sought is the minimum value of the difference in price set with the total search price obtained. The test results show the best aesthetic value is obtained at the value of Harmony Memory Consideration Rate (HMCR) of 0,95 with an average aesthetic percentage of 0,2691%.Keywords: aesthetic function, harmony search algorithms, parcelAbstrak. Parcel yang berisi berbagai macam barang, merupakan suatu hadiah yang diberikan kepada seseorang yang memiliki relasi dengan pemberinya. Isi dari parcel bervariasi, dapat berupa makanan, minuman, kue, buah, permen, maupun yang lain. Pada beberapa toko swalayan umumnya menjelang peringatan hari tertentu telah menyediakan Parcel dengan variasi isi di dalamnya dengan harga yang telah ditetapkan. Namun tidak jarang pembeli yang ingin mengemas Parcel mempunyai pandangan yang berbeda dengan isi parcel serta harga yang telah ditetapkan. Untuk memudahkan pencarian isi parcel yang berdasarkan harga tersebut maka digunakan algoritma Harmony Search. Pengembangan pencarian dilakukan dengan pertimbangan ukuran keranjang, kategori barang, serta prosentase masing-masing kategori. Evaluasi nilai aesthetic yang dicari adalah nilai minimum dari selisih harga yang ditetapkan dengan total harga pencarian yang didapatkan. Hasil pengujian menunjukkan nilai aesthetic terbaik didapatkan pada nilai Harmony Memory Consideration Rate (HMCR) 0,95 dengan presentase rata-rata aesthetic sebesar 0,2691%.Kata Kunci: algoritma harmony search, fungsi aesthetic, parcel